Multichannel WOLA algorithm in hydroacoustic monitoring and radio monitioring tasks and its computer simulation in MATLAB - Klionskiy, D. M.; Kaplun, D. I.; Voznesenskiy, A. S.; Gulvanskiy, V. V. (2014 2nd 2014 2nd International Conference on Emission Electronics (ICEE), 2014)
The present paper is devoted to the development, investigation, and computer simulation of a multichannel WOLA algorithm with regard to hydroacoustic monitoring and radio monitoring tasks in real time. Radio monitoring and hydroacoustic monitoring tasks are discussed and the main requirements to existing monitoring systems are provided. Several signal processing algorithms are considered including those based on a filter bank with complex modulation, polyphase filter bank, and a single-channel weighted overlap-add algorithm (WOLA-algorithm). The multichannel WOLA-algorithm is developed and clarified. High-performance software-hardware implementations on the basis of CPU and CUDA are compared and CUDA is shown to provide advantages for filter banks under study.